Unusual microtubule-dependent endocytosis mechanisms triggered by Campylobacter jejuni and Citrobacter freundii. - Oelschlaeger, T A (1993)
Bacterial invasion of six different human epithelial cell lines showed that some strains of the intestinal pathogen Campylobacter jejuni invaded intestinal cell lines at a level 10(2)-10(4) times higher than reported previously for other Campylobacter strains. Separately, urinary tract isolates of Citrobacter freundii triggered a high-efficiency invasion of bladder cells. Use of multiple inhibitors with known effects on eukaryotic cell structures/processes allowed us to define in these genetically distinct bacterial genera unusual bacterial invasion mechanisms that uniquely require microtubules but not microfilaments. Campylobacter jejuni strain 81-176 uptake into 407 intestinal cells and Citrobacter entry into T24 bladder cells was blocked by microtubule depolymerization and inhibitors of coated-pit formation but not by microfilament depolymerization. Inhibitors of endosome acidification had no significant impact on intracellular survival of Campylobacter jejuni or Citrobacter freundii, but monensin markedly reduced Citrobacter uptake. Epithelial cell invasion by both of these bacterial genera was dependent upon de novo bacterial protein synthesis but not upon de novo eukaryotic cell protein synthesis. In contrast to the T24 cell line-specific, strict microtubule-dependent uptake, Citrobacter entry into other cell lines was inhibited by both microtubule- and microfilament-depolymerization, suggesting that these bacteria encode two separate pathways for uptake (i, microtubule-dependent; ii, microfilament-dependent) that are cell line-specific and are recognized perhaps depending on the presence and abundance of appropriate eukaryotic receptors.